EPHEMERAL WINDOWS: Limits and Possibilities in the Brazil- USA, Regarding the South Atlantic (Global Journal of Human-Social Science, 2024)
The South Atlantic is a region that has been receiving growing attention due to the possibilities of changing its geopolitical balance mainly due to the increase in presence of China and to a lesser extent Russia Having Given the changing trend of the international configuration exemplified by real Inter- and Intra-state conflicts Ukraine Middle East African regions and potential South Sea China Central Asia Caucasus what would be the possibility of the Brazil increases its capacity to project power in region if by chance this clashed with the interests of the naval hegemonic power USA From the historical approach of two situations in which Brazil achieved positive arrangements with the USA in amid changing international configurations sought to establish an analytical standard from which some conclusions were established about the Current and future South Atlantic In summary the article points out that Negotiations between the USA and Brazil should only produce structural gains for both the parties when the fear of US regarding a Chinese enlargement becoming significant other than that eventual US concessions will be cosmetic and will not serve the interests strategies in Brazil
Keywords: BRAZIL-USA relationship; South Atlantic; hegemonic competition; China